Value of defibrillation threshold testing in children with nontransvenous implantable cardioverter defibrillators: Are routine DFT tests indicated?. Issue 8 (25th July 2020) - Backhoff, David; Müller, Matthias J.; Dakna, Mohammed; Leha, Andreas; Schneider, Heike; Krause, Ulrich; Paul, Thomas
Abstract: Background: Nontransvenous implanted cardioverter defibrillators (NT‐ICD) are used in infants and small children with life‐threatening ventricular tachyarrhythmias. With growth, shock vector shift may result in increase of defibrillation threshold (DFT) and fatal ICD failure. Objectives: To date, the only way to verify ICD function in children with NT‐ICD is repetitive DFT testing, which is potentially harmful and may even be life threatening. The aim of the study was to analyze data from NT‐ICD DFT testing to prospectively predict individual DFT. Patients and methods: Data from all pediatric patients with NT‐ICD implanted in our center from July 2004 to August 2019 were collected. Postoperative DFT testing was scheduled according to individual DFT but at least annually. Surgical revision of NT‐ICD was performed if DFT was > 25 J. Selected noninvasive parameters from DFT testing were analyzed as predictors for DFT using a logistic regression model. Results: A total of 46 children with NT‐ICD underwent a total of 402 DFT tests. Mean age at implantation had been 5.4 ± 3.3 years, mean follow‐up was 5.6 ± 3.7 years in 5 (1%) DFT testing, maximum device output failed, and external defibrillation was necessary. A retrospective multiple mixed logistic regression model was able to predict a DFT ≥25 J (area under the curve [AUC] = 0.836). However, when prospectively validated the model showed moderate performance only (AUC = 0.70). Conclusion: A significant number of NT‐ICD failures were detected by serial DFT testing. Serial DFT testing was safe in pediatric patients with an NT‐ICD as all induced arrhythmia could be terminated. Prediction of DFT with noninvasive markers remains difficult and might help to schedule intervals for routine DFT tests to avoid unnecessary tests.